EFFICACY OF EARLY FLUID RESUSCITATION IN ACUTE PANCREATITIS - Aliya Nasim; Hafiz Muhammad Talha Nawaz; Saifullah Shafiq; Anisa Khan; Muhammad Shoaib; Aitisam Ullah Shah; Muhammad Saad Ahmad; Shawwal Amjad; Atiq Ur Rehman (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study intended to assess the influence of early administration of fluids on the clinical results of individuals admitted to the hospital for acute pancreatitis. We conducted a retrospective analysis on a cohort of 701 patients diagnosed with acute pancreatitis at Hayatabad Medical Complex, Peshawar, Pakistan. We included 434 of total non-transferred patients after removing transferred patients and those with incomplete data. We classified patients into two groups, early resuscitation (340 patients) and late resuscitation (94 patients), based on the amount of intravenous fluids administered within first 24 hours. The main outcomes assessed were the occurrence of (SIRS), organ failure, admission to the (ICU), duration of hospitalization, and mortality. The statistical analyses conducted in this study involved t-tests, chi-square tests, and multivariate logistic regression. Early resuscitation resulted in dramatically reduced rates of (SIRS) and organ failure at 24, 48, and 72 hours, decreased (ICU) admissions, and shorter hospital stays. In terms of mortality, intra-abdominal infections, or necrosis, no important differences were detected on CT scans. Subgroup analysis showed that the positive results of early resuscitation were especially distinguished in the groups of patients with interstitial illness on admission but were restricted in those with severe disease: positive response to early fluid intervention was particularly marked in patients with interstitial disease on admission, but patients with severe disease showed a restricted positive response to early fluid intervention. Initiation of fluid resuscitation early in the course of acute pancreatitis is associated with better clinical outcomes, particularly in patients with interstitial disease. That is essential and needs to be done early in any clinical setting.